(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores methodological approaches to solving metric problems in the subject of Descriptive Geometry. It analyzes both theoretical and practical ways of developing students’ spatial thinking, deep understanding of projection laws, and graphic representation skills when solving metric problems. The research demonstrates the effectiveness of a step-by-step methodical approach and visual tools used in the teaching process.